2019
DOI: 10.1016/j.jss.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Personality Testing May Identify Applicants Who Will Become Successful in General Surgery Residency

Abstract: Introduction Identification of successful general surgical residents remains a challenging endeavor for program directors (PD) with a national attrition of approximately 20% per year. The Big 5 Personality traits and the Grit Scale have been extensively studied in many industries and certain traits are associated with professional or academic success. However, their utility in surgery resident selection is unknown. Methods We performed a retrospective review of all categorical surgery residents (n=34) at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…The students in our study who had a preference for surgical specialties could be described as less modest, more extroverted, more diligent, more organized, and overall less emotional, than their clinical counterparts. Hughes et al (6) analyzed the association of BFM scores with performance in surgical specialties. They found that higher scores for the extroversion, conscientiousness, and emotional stability scales could predict better performance during surgical training.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The students in our study who had a preference for surgical specialties could be described as less modest, more extroverted, more diligent, more organized, and overall less emotional, than their clinical counterparts. Hughes et al (6) analyzed the association of BFM scores with performance in surgical specialties. They found that higher scores for the extroversion, conscientiousness, and emotional stability scales could predict better performance during surgical training.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have assessed the personality traits of medical personnel or medical students (6,14) . In the present study, we aimed to identify any associations between the HEXACO personality traits and the medical students' preferred specialty.…”
Section: Several Models Have Been Used To Analyze Personality In Medimentioning
confidence: 99%
See 1 more Smart Citation
“…The type of interview may vary from program to program. 3,4 With the understanding that interviews may be structured (the person or team conducting the interview utilizes a standardized set of questions that focuses on the candidate's experiences and abilities) or unstructured (the approach is more conversational and unscripted), and the caveat that criteria defining an outstanding interview are entirely subjective, we believe that adherence to this list of "Ten Commandments" for the interviewee would be advantageous for most applicants.…”
Section: The Ten Commandments Of the Residency Interview The Ten Commmentioning
confidence: 99%
“…The FFM suggests that the human personality and behavior could be explained by the exploration of five factors: Openness to Experience/intellect, Conscientiousness, Extraversion, Agreeableness, and Neuroticism (also known as emotional stability) [7,8]. Over the years, several measurement tools have been proposed for personality studies using the FFM, such as the Zuckerman-Kuhlman personality questionnaire [5,9], the Eysenck Personality Questionnaire (Revised) [10], the Big Five Inventory [11][12][13], and finally the NEO Personality Inventory [14][15][16]. These inventories analyze the five factors and their underlying facets and provide an interpretation of human nature.…”
Section: Introductionmentioning
confidence: 99%